Epidemiology of Comorbid Conditions Among Adults 50 Years and Older With Traumatic Brain Injury. Issue 1 (January 2018) - Kumar, Raj G.; Juengst, Shannon B.; Wang, Zhensheng; Dams-O'Connor, Kristen; Dikmen, Sureyya S.; O'Neil-Pirozzi, Therese M.; Dahdah, Marie N.; Hammond, Flora M.; Felix, Elizabeth R.; Arenth, Patricia M.; Wagner, Amy K.
Abstract : Objectives: Aging individuals with traumatic brain injury (TBI) experience multiple comorbidities that can affect recovery from injury. The objective of this study was to describe the most commonly co-occurring comorbid conditions among adults 50 years and older with TBI. Setting: Level I Trauma centers. Participants: Adults 50 years and older with moderate/severe TBI enrolled in the TBI-Model Systems (TBI-MS) from 2007 to 2014 ( n = 2134). Design: A TBI-MS prospective cohort study. Main Measures: International Classification of Disease–9th Revision codes collapsed into 45 comorbidity categories. Comorbidity prevalence estimates and trend analyses were conducted by age strata (50-54, 55-64, 65-74, 75-84, ≥85 years). A dimension reduction method, Treelet Transform, classified clusters of comorbidities that tended to co-occur. Results: The 3 most commonly occurring comorbid categories were hypertensive disease (52.6/100 persons), other diseases of the respiratory system (51.8/100 persons), and fluid component imbalances (43.7/100 persons). Treelet Transform classified 3 clusters of comorbid codes, broadly classified as (1) acute medical diseases/infections, (2) chronic conditions, and (3) substance abuse disorders. Conclusion: This study provides valuable insight into comorbid conditions that co-occur among adults 50 years and older with TBI and provides a foundation for future studies to explore how specific comorbidities affect TBI recovery. Abstract : Supplemental Digital Content is Available in the Text.